Faktor Risiko Berhubungan dengan Kejadian Kanker Payudara Wanita: Risk Factors Associated with the Incidence of Female Breast Cancer - Susi Purwanti; Nursari Abdul Syukur; Cristinawati B/R Haloho (Jurnal Bidan Cerdas, 2021)
Introduction: Breast cancer or breast maligna is one of the second high death causes after heart coronary and tend to increase. Purpose of this study is to understand the risk factors of breast cancer in Dr.Kanujoso Djatiwibowo Balikpapan hospital. Methods: This study is quantitaive, analytic study with case control design and used Chi-Square, this study used 48 samples women with breast cancer (1:1) with purposive sampling. Bivariate analysis using chi-Square test, with OR (Odd Ratio or chance) using 95%confidence level. Results: The results showed a significant relationship between obesity (OR 11.7; p<0.001), hormonal family planning (OR=4.1; p=0.019), history of breastfeeding (OR=0.3; p=0.035) and family history (OR=4.5; p=0.017) with the incidence of breast cancer. Conclusion: obesity is the dominant risk factor where obese women are 11.7 times at risk of breast cancer.